1996
DOI: 10.1111/j.1651-2227.1996.tb13891.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asthma at school age: a clinical population‐based study in eastern Finland

Abstract: A questionnaire aimed at screening and identifying patients with asthmatic symptoms was sent to the parents of 2011 children aged 7 to 12 years; 1633 (81%) returned the questionnaire. A clinical examination was given to 165 symptomatic and 82 non-symptomatic children. The children were classified into three groups: 1, clinical asthma (n = 43); 2, other symptoms from lower airways (OSLA) (n = 34); 3, healthy children (n = 170). The prevalences of asthma and OSLA in the whole source population (n = 1633) were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
57
2

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 18 publications
10
57
2
Order By: Relevance
“…Recently, a prevalence of 4.4% of doctor-diagnosed asthma was reported among children aged 7-12 yrs in Kuopio, East Finland [6,19], which is consistent with the present results. In Turku, a prevalence of 2.5% of doctor-diagnosed asthma was recently reported among adolescents [16]; which was less than half of that in the present study (7%).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Recently, a prevalence of 4.4% of doctor-diagnosed asthma was reported among children aged 7-12 yrs in Kuopio, East Finland [6,19], which is consistent with the present results. In Turku, a prevalence of 2.5% of doctor-diagnosed asthma was recently reported among adolescents [16]; which was less than half of that in the present study (7%).…”
Section: Discussionsupporting
confidence: 93%
“…In Finland, the prevalence of childhood asthma has been reported to be lower than in many European countries, and in East Finland lower than in other parts of the country [5]. These variations may be due to true differences in prevalence, but may also be due to differences in the diagnostic criteria and study methods used.Few surveys have included tests for bronchial hyperresponsiveness or clinical examinations, due to their high cost [6][7][8]. Thus, symptom questionnaires have been the principal instrument for measuring asthma prevalence in community surveys [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the Finnish Birth Cohort study, designed to detect the association between asthma and mode of delivery, the incidence of asthma was comparable to that of earlier reports in Finland (33) and elsewhere (34,35). These results again showed that children born by caesarean section had more asthma and positive skin prick tests than those born by normal vaginal delivery.…”
Section: Discussionsupporting
confidence: 74%
“…11 Asthma was considered to be present when 1) the patient was on continuous maintenance medication for asthma or when 2) she or he had had repeated (Ն2) episodes of wheezing and/or prolonged (Ն4 weeks) cough apart from infection during the preceding 12 months and the exercise challenge test was regarded as positive. 12 The allergens tested by SPTs were (the outdoor allergens) birch, common alder, timothy grass, meadow grass, and mugwort pollens and spores of Cladosporium herbarum; and (the indoor allergens) cat and dog epithelial dander and home dust mites Dermatophagoides pteronyssinus and D farinae. The concentration of a nonstandardized extract of C herbarum spores was 1:20 wt/vol.…”
Section: Methodsmentioning
confidence: 99%